Desaguamento de lodo biológico de estações de tratamento de esgoto sanitário: uma abordagem microbiológica com Acidithiobacillus thiooxidans e Rhodotorula mucilaginosa - Gonçalves, Jamile (Universidade Federal de São Carlos, 2024)
Sludge from Sewage Treatment Plants (STPs) has high moisture content, a factor that adversely affects its disposal or reuse. In this regard, bioleaching, already known for its effectiveness in the treatment of metals, has demonstrated the simultaneous ability to promote dewatering. However, the high concentration of dissolved organic matter in the sludge has an inhibitory effect on microorganisms commonly used in this process, but when combined with acid-tolerant heterotrophic microorganisms, this effect can be minimized. Therefore, this study evaluated the dewatering of sludge from two STPs in tests with the bacterium Acidithiobacillus thiooxidans and the yeast Rhodotorula mucilaginosa. Different inoculum concentrations, performance of the supernatants of the bacteria and yeast, as well as commercial synthetic surfactants were compared. Finally, the effect of coinoculation of the bacteria and yeast on the dewatering process was evaluated. Dewatering was measured by filtration time (TTF), specific filtration resistance (SRF) and extracellular polymeric substances (EPS) tests. In the treatment with A. thiooxidans, there was a greater reduction in TTF (8.3 ± 0.2 min) with 15% inoculum, concomitantly with a reduction in the concentration of proteins bound in EPS (71.3%, compared to the control). With R. mucilaginosa, a lower TTF (1.1 ± 0.2 min) was obtained with the lowest inoculum concentration (5%) and the percentage of proteins in the bound fraction was less than 10% in the three concentrations evaluated. Both supernatants, from bacteria and yeast, promoted improved dewatering (TTF of 1.5 ± 0.1 min and 1.2 ± 0.1 min, respectively). However, the most efficient dewatering was obtained with the co-inoculation of A. thiooxidans (15%) and R. mucilaginosa (5%), resulting in a TTF of 14 ± 2.4 seconds, 98.7% lower than the control sludge (17.9 ± 0.6 min), with a concentration of bound proteins in EPS 79% lower than the control. Kendall's correlation analysis demonstrated a positive correlation between the TTF and the concentration of proteins in the bound fraction of EPS, reinforcing the hypothesis that the reduction of bound proteins is favorable to dewatering. The co-inoculation test was replicated with sludge from another STP, demonstrating its applicability in other types of sludge. The combined supernatants of A. thiooxidans (15%) and R. mucilaginosa (15%), in turn, reduced the TTF by 90.0% compared to the control, and although it presents similar performance to co-inoculation, its practical application can be advantageous by allowing the reuse of biomass and dewatering potential in a shorter treatment time.
Dewatering of biological sludge from sewage treatment plants: a microbiological approach with Acidithiobacillus thiooxidans and Rhodotorula mucilaginosa
Keywords: Biorremediação; Substâncias Poliméricas Extracelulares; Metais; Diversidade Microbiana; Bioremediation; Extracellular Polymeric Substances; Metals; Microbial Diversity; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::MICROBIOLOGIA APLICADA E ENGENHARIA SANITARIA